Training Needs of Dairy Farm Instructors of the Dairy Development Department of Kerala - Vimal Raj Kumar N (Department of Extension, College of Veterinary and Animal Sciences, 2003)
The objectives of the study were to identify the training needs of the Dairy Farm Instructors (DFls) of Dairy Development Department of Kerala and find out the determinants of their training needs. The data were collected through questionnaires to which 75 DFls responded. Information technology was the most preferred major subject matter domain for training followed by milk and milk products, dairy cattle production and management, dairy extension, professional management and I fodder production and management. Among the socio-personal characteristics, the training exposure and role perception of the respondents had significant relationship with the training need. Both the role perception and training need of most of the respondents were medium only. For all the domains, institutional type of training as well as trainers from outside the parent organization but within the state were preferred the most. Demonstration was the most preferred method of training for most of the domains. The most preferred periodicity for the trainings of one to seven days duration was six months, those of eight to fourteen days was one year and those of fifteen to thirty days and more than a month was more than a